The sigma subunit of Escherichia coli RNA polymerase senses promoter spacing. - Dombroski, A J (1996)
The promoters recognized by sigma 70, the primary sigma of Escherichia coli, consist of two highly conserved hexamers located at -10 and -35 bp from the start point of transcription, separated by a preferred spacing of 17 bp. sigma factors have two distinct DNA binding domains that recognize the two hexamer sequences. However, the component of RNA polymerase recognizing the length of the spacing between hexamers has not been determined. Using an equilibrium DNA binding competition assay, we demonstrate that a polypeptide of sigma 70 carrying both DNA binding domains is very sensitive to promoter spacing, whereas a sigma 70 polypeptide with only one DNA binding domain is not. Furthermore, a mutant sigma, selected for increasing transcription of the minimal lac promoter (18-bp spacer), has an altered response to promoter spacing in vivo and in vitro. Our data support the idea that sigma makes simultaneous, productive contacts at both the -10 and the -35 regions of the promoter and discerns the spacing between these conserved regions.